Development of Light Weight Material as Filler Element for High Rise Building Using ETABS Software - Singhai, Ankita; Satbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2019)
Solid structures are inclined to tremor because of mass of the structures. essential utilization of auxiliary lightweight cement (SLWC) is to decrease the dead heap of a solid structure, which enables the basic fashioner to diminish the span of the basic individuals like pillar, segment, and footings which results in decrease of seismic tremor powers on the structure. This examination is an endeavor to anticipate the seismic reaction of a ten-storied fortified solid casing with the utilization of lightweight cement. A very much planned ten story precedent is taken for study. The structure is demonstrated with ETABS programming, and examination is completed with typical weight and lightweight cement. The fundamental rationale of our investigation is to allocate a light weight concrete in a tall building structure, where we can check its positive and negative impact on the strength of the structure. Likewise to legitimize the auxiliary cost decrease because of usage of light weight material.
Keywords: ETABS; Structural Analysis; Forces; Cost Analysis; Lateral Forces; Displacement